Language Learning Strategies Used By Vocational Study Program Students - Made Rudiastika; Rima Andriani Sari; Ni Putu Era Marsakawati (International Journal of Language and Literature, 2023)
This study aims to identify the language learning strategies used by students and the factors that affect the selection of these strategies in the vocational study program of the Faculty of Languages and Arts at a public university in Bali. This research uses a mixed method, namely quantitative and qualitative approaches. The participants of this study are 50 students from two study programs, namely Visual Communication Design and United Kingdom for Business and Professional Communication. Data was collected through the Strategy Inventory for Language Learning (SILL) version 7.0 questionnaire developed by Oxford, which has been adapted and validated by two experts. This questionnaire consists of 50 statements divided into six categories of strategies, namely memory, cognitive, compensatory, metacognitive, affective, and social. The results showed that the most frequently used strategy by students was the metacognitive strategy (M = 4.00), followed by cognitive and memory strategies, while the least used strategy was the affective strategy (M = 3.53). In addition, the results of this study also show that the factors of the study program, academic achievement index, and student motivation affect the use of language learning strategies. Therefore, it is important to teach students the right language learning strategies, as they can help improve their learning outcomes.